LumiLoc: A Low-Light-Optimized Visual Localization Framework for Autonomous Drones - Ruokun Qu; Zhiyuan Wang; Yelu Liu; Chenglong Li; Hui Jiang; Chen Fang (Aerospace)
In low-light conditions, UAV localization faces substantial challenges due to reduced visibility, elevated noise levels, and diminished contrast. To address these issues, we propose a low-light-optimized visual localization framework that integrates an attention-based image enhancement module, a robust feature extraction network tailored for degraded environments, and a lightweight pose estimation algorithm that fuses geometric and convolutional features. Extensive evaluations on both real-world and synthetic low-light datasets reveal significant improvements in accuracy, noise resilience, and adaptability to dynamic lighting. Moreover, experimental results validate the framework’s feasibility for applications in night operations, urban air traffic management, and disaster response, thereby effectively overcoming the critical limitations of UAV positioning under low-light conditions.